Exposure of migratory shorebirds to organophosphorus and carbmate pesticides at migratory stopover and non-breeding sites in the western hemisphere - Strum, Khara M. (Kansas State University, 2008)
Monitoring programs indicate that numerous shorebird populations are subject to on-going declines. The U.S. Shorebird Conservation Plan lists twenty-seven shorebird species as species of high concern and seven as highly imperiled, including the Buff-breasted Sandpiper (Tryngites subruficollis). One hypothesis for ongoing population declines is exposure to toxic chemicals and pollutants. The purpose of this project was to characterize plasma cholinesterases (ChEs) of migratory shorebirds and address potential exposure to organophosphorus (OP) and carbamate (CB) pesticides. Consumption or contact with these pesticides can cause mortality and a variety of sub-lethal effects. Buff-breasted Sandpipers and other upland shorebirds are particularly likely to encounter agrochemicals due to their habitat use at the non-breeding grounds. I sampled migratory shorebirds over three seasons, during north- and southbound migration in 2006 and 2007 in Texas, Kansas, and Nebraska and during the non-breeding season in 2007 in Argentina, Uruguay, and Paraguay. I collected blood samples and footwashings from reference sites, where OP and CB pesticides were not used, and agricultural sites, where these two insecticides were recommended for control of crop pests. I assessed several variables known to affect plasma ChE activity including body size, date of capture, time of capture, condition, sex, and region. Small-bodied species had higher levels of ChE activity in plasma than large-bodied species. Plasma ChE activities varied with date of capture in 3 of 5 species sampled in North America. Sex differences were significant in 1 of 4 species tested. Plasma acetylcholinesterase (AChE) activity was higher among White-rumped Sandpipers sampled in North America but there was no difference between regions among Buff-breasted Sandpipers. Time of capture and individual condition did not affect plasma ChE activity. Estimates of exposure to ChE inhibitors were addressed in five species. Plasma AChE and butyrylcholinesterase (BChE) activities of Buff-breasted Sandpipers were lower at agricultural sites in South America but BChE activity was higher at agricultural sites in North America. There were no differences between sites in four other species tested. A meta-analysis across all species indicated that in 4 of 6 comparisons habitat type had a negative effect on AChE activity consistent with exposure to ChE inhibitors but there was a regional positive effect of agricultural habitat on BChE activity in North America. Comparison of body mass between sites suggested that use of habitats with potential pesticide application did not affect mass gain. Project results suggest that 1 of 5 shorebird species tested was exposed to ChE-inhibiting pesticides at the non-breeding grounds and future monitoring is necessary to assess potential effects at the population level. This study highlights the importance of complete sampling and addressing variability in plasma ChEs before making estimates of exposure to OP and CB pesticides. It provides the first estimates of migratory shorebird exposure to OP and CB pesticides, a potential conservation issue. Future research should include continued monitoring of Buff-breasted Sandpiper ChE levels and habitat use. Other sources of anthropogenic declines such as habitat loss and illegal hunting should be investigated for species that did not show evidence of exposure.
Keywords: Carbamate; Organophosphate; cholinesterase; ecotoxicology; waders; insecticides; Biology, Ecology (0329)